Transformasi Tata Kelola Kelapa Sawit Berkelanjutan Di Tingkat Daerah: Studi Kebijakan Rad-Ksb Provinsi Jambi: Transformasi Tata Kelola Kelapa Sawit Berkelanjutan Di Tingkat Daerah: Studi Kebijakan Rad-Ksb Provinsi Jambi - Muhammad Abdul Aziz; Subhan, Ahmad; Muchlis, Fuad; Betharia, Roro (Jurnal Khazanah Intelektual, 2026)
The development of Indonesia’s palm oil plantation sector faces complex sustainability challenges, including low smallholder productivity, limited land legality, and weak compliance with the Indonesian Sustainable Palm Oil (ISPO) standards. In Jambi Province, these issues have prompted the local government to establish the Regional Action Plan for Sustainable Palm Oil (RAD-KSB) as a governance instrument to strengthen institutional capacity, improve farmer performance, and enhance supply chain management. This study aims to analyze the implementation of the RAD-KSB policy and its contribution to strengthening the sustainability of palm oil farming at the subnational level. A descriptive qualitative design with an intrinsic case study approach was applied, using key informant interviews, questionnaires, and document reviews. Data were analyzed using George C. Edward III’s policy implementation model, which assesses communication, resources, disposition, and bureaucratic structure through a Likert scale. The results indicate that resources (3.8) and bureaucratic structure (3.5) are categorized as good, supported by extension services and multi-stakeholder forums, while communication (2.7) and implementer disposition (2.6) remain moderate due to limited regulatory literacy and misaligned staff competencies. Significant land legality gaps also hinder ISPO certification. It is concluded that improving the effectiveness of RAD-KSB requires spatial data integration, digital communication systems, bureaucratic simplification, and enhanced implementer capacity and incentives to achieve sustainable palm oil governance at the regional level